Somatic mutations substantially increase the per‐generation mutation rate in the conifer Picea sitchensis - Hanlon, Vincent C. T.; Otto, Sarah P.; Aitken, Sally N. (Evolution letters, 2019)
The rates and biological significance of somatic mutations have long been a subject of debate. Somatic mutations in plants are expected to accumulate with vegetative growth and time, yet rates of somatic mutations are unknown for conifers, which can reach exceptional sizes and ages. We investigated somatic mutation rates in the conifer Sitka spruce (Picea sitchensis (Bong.) Carr.) by analyzing a total of 276 Gb of nuclear DNA from the tops and bottoms of 20 old‐growth trees averaging 76 m in height. We estimate a somatic base substitution rate of 2.7 × 10−8 per base pair within a generation. To date, this is one of the highest estimated per‐generation rates of mutation among eukaryotes, indicating that somatic mutations contribute substantially to the total per‐generation mutation rate in conifers. Nevertheless, as the sampled trees are centuries old, the per‐year rate is low in comparison with nontree taxa. We argue that although somatic mutations raise genetic load in conifers, they generate important genetic variation and enable selection both among cell lineages within individual trees and among offspring.